Veteran welfare past and present: a sociological analysis of the Civil War Petitions, 1642–1718 - Hopper, Andrew; Pells, Ismini; Bricknell, Martin (Frontiers in Sociology, 2025)
This article examines the idea of a social contract between the armed forces and the state through a cross period comparison between the United Kingdom in recent years and England and Wales during the mid-seventeenth century. In doing so, it provides an analysis, grounded in sociological theory, of an early military pension scheme evidenced by thousands of surviving petitions for military welfare made by the maimed soldiers, war widows and orphans of the British Civil Wars (1639–1652). Through the findings of the Civil War Petitions project (https://www.civilwarpetitions.ac.uk), this article provides an overview of how seventeenth-century soldiers and war widows operated from the perspective of successive government regimes, administrators, and recipients. The project demonstrates that the extent of military welfare for maimed soldiers, war widows and orphans was greater than previously supposed. In three thematic sections, this article discusses the conditions, process, and purpose of granting military pensions and monetary support. This national provision of military welfare was an important early milestone in securing popular participation in the formation of the modern fiscal-military state. Throughout, these analyses are compared with the experience of the United Kingdom's Armed Forces today, in order to assess similarities and differences with the seventeenth century, linking the experience of veteran welfare in the past through to the present. In the seventeenth century, those poor maimed soldiers and war widows who were denied pensions often found themselves dependent on parish poor relief and the charity of their neighbors. In contrast, today many veterans benefit from well-organized UK military charities, which help to compensate for the shortcomings of state welfare. The activities of these organizations continue to support a form of social contract between the armed forces and the civilian population, where the state is not always the primary link or sole provider of support. New theories of the social contract should take this plurality into account.